OTTOMAN ECONOMIC THOUGHT FROM ANCIENT TO MODERN TIMES - Kenan DEMİR (Fırat University, 2019)
Ottoman ancient economic thinking had a complex structure in which political, religional, martial and administrational thoughts played their respective parts and the state ran all the economic activity. Ancient economic thinking had been implemented in accordance with social and statist policies, and the policies implemented by the state had been in the provisionist, traditionalist and fiscalist lines. Ottoman economy experienced several crises starting from the 16. Century and administrators in the state put forward numerous explanations in order to eradicate these crises. In the layihas (written petitions) which were presented to the padishahs (sovereigns), different solutions such as rehabilitation of the tımar system, reduction in the state expenditures and boosting state incomes had been suggested. Since 18. Century, solutions to the crises the state experienced had been sought abroad and in the West for the first time, though economic policies that state officials implemented stayed in the course of ancient economic thought. 19. Century is the period in which it was understood that ancient policies were not solutions to the existing economic problems of the state and it was thought that Western economic policies is the right path to pursue for the economic advancement. Western experts in the Ottoman Empire and state officials sent to Western countries as ambassadors gave voice to modern economic thought in the country for the first time. Since 1830s modern economic thought had been prescribed for the Ottoman development. State officials -Mustafa Reşit Pasha, Sadık Rıfat Pasha, Ali Pasha, Fuat Pasha and Ahmet Cevdet Pasha- had liberal and cameralist thoughts and shaped economic policies of the state in line with these thoughts.